Crystallization in supercooled liquid Cu: Homogeneous nucleation and growth - E, J. C.; Wang, L.; Cai, Y.; Wu, H. A.; Luo, S. N. (The Journal of chemical physics, 2015)
Homogeneous nucleation and growth during crystallization of supercooled liquid Cu are investigated with molecular dynamics simulations, and the microstructure is characterized with one- and two-dimensional x-ray diffraction. The resulting solids are single-crystal or nanocrystalline, containing various defects such as stacking faults, twins, fivefold twins, and grain boundaries; the microstructure is subject to thermal fluctuations and extent of supercooling. Fivefold twins form via sequential twinning from the solid-liquid interfaces. Critical nucleus size and nucleation rate at 31% supercooling are obtained from statistical runs with the mean first-passage time and survival probability methods, and are about 14 atoms and 1032 m−3s−1, respectively. The bulk growth dynamics are analyzed with the Johnson-Mehl-Avrami law and manifest three stages; the Avrami exponent varies in the range of 1–19, which also depends on thermal fluctuations and supercooling.